Childcare burden and changes in fertility desires of mothers during the COVID-19 pandemic - Golovina, Kateryna; Nenko, Ilona; Marcinkowska, Urszula Maria (Frontiers in Psychology, 2023)
Objectives: Previous studies have documented a decline in fertility desires and intentions following the COVID-19 outbreak, but the reasons for this decline are not well understood. This study examined whether childcare burden on mothers during the lockdown and quarantines, COVID-related stress, and COVID exposure were associated with a change in the desired number of children. Methods: The survey was conducted online, in Poland from April to July 2021 on a sample of 622 non-pregnant mothers without diagnosed infertility. Results: Associations were observed between childcare responsibilities during the quarantine and fertility desires: mothers who solely or mainly took care of their children during the quarantine(s) were more likely to decrease their desired number of children ([adjusted] aOR = 1.91, 95% CI = 1.16–3.15). Mothers with higher levels of COVID-related stress (aOR = 1.81, 95% CI = 1.48–2.22) and a greater COVID exposure index (aOR = 1.39, 95% CI = 1.12–1.72) were more likely to decrease their fertility desires. Conclusions: Higher childcare burden during quarantines was related to a lower desired number of children among mothers. Both greater COVID-related stress and COVID exposure were associated with fertility desires, regardless of childcare responsibilities during the pandemic.